A 48 year old male with wandering pleural effusion and pulmonary infiltration. (February 2021) - Ning, Weiwei; Yang, Limin; Chen, Yanbin; Chen, Cheng
We reported a case of pulmonary paragonimiasis presenting as wandering pleural effusion and pulmonary infiltration. The patient had an explicit history of eating raw freshwater crabs 6 months earlier, and a test for serum antibodies to paragonimus was positive. This case illustrates the complex nature of pathological processes and immunological responses in the lungs and highlights the need to consider the existence of paragonimus infection.